Integrative Approaches to Prostate Disease Management: Nutrition, Exercise, and Lifestyle Modifications - Patrick Maduabuchi Aja; Peter Chinedu Agu; Angela Mumbua Musyoka; Wisdom Ngwueche; Joseph Uche Odo; Esther Ugo Alum; Ilemobayo Victor Fasogbon; Mbyemeire Herbert; Ejike Daniel Eze (American Journal of Men's Health)
Prostate-related conditions, including benign prostatic hyperplasia, prostatitis, and prostate cancer, represent significant health concerns, particularly among aging men. This study utilized a comprehensive review of existing literature and case studies to explore the effectiveness of integrative approaches, emphasizing nutrition, exercise, and lifestyle modifications, in managing prostate diseases. Data were collected from peer-reviewed journals, clinical trials, and meta-analyses focusing on dietary patterns, physical activity, and complementary therapies. The findings were synthesized to provide evidence-based recommendations. Results highlight that plant-based diets, rich in fruits, vegetables, whole grains, and healthy fats, demonstrate protective effects against prostate conditions, while diets high in saturated fats and processed foods increase risk. Specific bioactive compounds,such as lycopene, omega-3 fatty acids, and polyphenols, were linked to reduced disease progression. Physical activity emerged as a key component, enhancing hormonal balance, reducing inflammation, and improving survival rates in prostate cancer patients. Aerobic and resistance exercises were particularly effective in mitigating treatment side effects such as fatigue and muscle loss. Stress-reduction techniques, including mindfulness and yoga, alongside moderated alcohol consumption, further improved psychological well-being and overall prostate health. Integrative approaches, combining conventional treatments with holistic care, demonstrated enhanced outcomes by addressing the physical, emotional, and social dimensions of prostate disease. Emerging fields such as nutrigenomics and natural products offer opportunities for personalized interventions, paving the way for innovative management strategies. This study underscores the potential of integrative methods to improve disease outcomes, prevent progression, and enhance the quality of life for men affected by prostate conditions, advocating for their inclusion in prostate disease management protocols.